ESTUDO SOBRE OS FAXINAIS LAGEADO DE BAIXO E LAGEADO DOS MELLO – PR: A CONSTRUÇÃO DE CONHECIMENTO A PARTIR DA ECOLOGIA SOCIAL COMO SUBSÍDIO PARA UM PROJETO DE TURISMO COMUNITÁRIO - Ferreira, Patricia (2008)
Environmental and cultural diversity represents an intrinsic value for itself, independently from its incorporation into a globalized urban-industrial culture. To counter the actual global socio-environmental crisis, it is important to better understand the rationalities and lifestyle modes which are closer to a sustainable dealing with nature, as it is, for example, the case of traditional societies. A two-sided learning process between proprietors of traditional knowledge and of scientific knowledge can lead to the improvement of life quality in traditional communities and can help to avoid that the incorporation of these communities into the market economy causes the degradation of its diversity. In this sense, we are on the search for a social ecology. This research evaluates communitarian tourism as a means to contribute to cultural conservation and the improvement of life quality of traditional societies, as well as the stabilization of biodiversity in its territories. It refers to the people and land properties of Faxinal communities in Paraná. It tries to avoid an imposition of the researcher’s perspective throughout the analysis by using methods of participant observation and unstructured interviews in the communities of “Lageado de Baixo”, located in the municipality of Mallet, and “Lageado de Mello”, in the municipality of Rio Azul. These Faxinais dispose of various resources to develop tourist activities, among others: extensive walks on the interior tracks of the Faxinais, bird and animal watching, contemplation of landscape and vegetation, listening to the narratives of the local population, observation of their differentiated lifestyles. As such, communitarian tourism is considered a tool of a two-side learning experience between visitors and traditional communities and, therefore, can be regarded as a means to preserve the Faxinais of Paraná.